2009
DOI: 10.1021/jf902173d
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Micro-Oxygenation and Wood Type on the Phenolic Composition and Color of an Aged Red Wine

Abstract: Many studies have recently been published focused on the effects of micro-oxygenation on the quality of wines, its application modes, and doses, etc. However, there are still few scientific papers on how previously micro-oxygenated wines perform during storage or barrel aging. This study focused on the evolution of the phenolic composition, especially of anthocyanins, and color, together with astringency and tannins, during micro-oxygenation before barrel aging. In addition, to evaluate whether wine evolution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 28 publications
4
30
1
Order By: Relevance
“…These results were very similar to those found by Revilla and González-Sanjosé (2001) with Tempranillo wines stored for two years in bottle. These results contrast again with those reported by Monagas, Gómez-Cordovés, and Bartolome (2005) and Sánchez-Iglesias et al (2009), who observed a decrease in the concentration of pyruvic anthocyanins during storage in bottle and wine ageing respectively. However, Pérez-Magariño and González-Sanjosé (2004) and Alcalde-Eon, Escribano-Bailón, Santos-Buelga, and Rivas-Gonzalo (2006) found an increase in pyranoanthocyanin levels during the first year of barrel ageing.…”
Section: Resultscontrasting
confidence: 93%
See 1 more Smart Citation
“…These results were very similar to those found by Revilla and González-Sanjosé (2001) with Tempranillo wines stored for two years in bottle. These results contrast again with those reported by Monagas, Gómez-Cordovés, and Bartolome (2005) and Sánchez-Iglesias et al (2009), who observed a decrease in the concentration of pyruvic anthocyanins during storage in bottle and wine ageing respectively. However, Pérez-Magariño and González-Sanjosé (2004) and Alcalde-Eon, Escribano-Bailón, Santos-Buelga, and Rivas-Gonzalo (2006) found an increase in pyranoanthocyanin levels during the first year of barrel ageing.…”
Section: Resultscontrasting
confidence: 93%
“…This fact has been confirmed in other studies (Sánchez-Iglesias, González-Sanjosé, Pérez-Magariño, Ortega-Heras, & González-Huerta, 2009). In the two vintages the formation of new polymeric pigments increased during the vinification and storage process (Tables 2 and 3).…”
Section: Resultssupporting
confidence: 82%
“…As an example, sun‐exposed berries increased in quercetin‐3‐glucoside concentration but resveratrol was not detected (Haselgrove and others 2000), while in another study Price and others (1995) demonstrated that caftaric acid, catechin, and epicatechin concentrations were low in sun‐exposed grapes. In terms of vinification practices, higher fermentation temperatures (Sacchi and others 2005), application of fining agents (Castillo‐Sanchez and others 2008) or different aging methods such as oak aging (Sanchez‐Iglesias and others 2009) all influence the phenolic content in wine. Because of the complexity of these factors, it is difficult to consistently increase concentrations of specific phenolic compounds simultaneously.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of MOX reportedly increases colour stability through the formation of pigmented polymers and decreases astringency; however, results vary greatly depending on wine composition, timing of MOX application, dosage and temperature (Gomez-Plaza and Cano-Lopez 2011, Oberholster et al 2015). Combination treatments of MOX with oak staves are also more effective than MOX alone in accelerating wine ageing as well as producing favourable sensory attributes (Cano-Lopez et al 2008, Sánchez-Iglesias et al 2009. Combination treatments of MOX with oak staves are also more effective than MOX alone in accelerating wine ageing as well as producing favourable sensory attributes (Cano-Lopez et al 2008, Sánchez-Iglesias et al 2009.…”
Section: Impact Of Winemaking Practices On Tannins 609mentioning
confidence: 99%